2022
DOI: 10.3390/molecules27144450
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Antifungal Evaluation of Novel Pyrylium Salt In Vitro and In Vivo

Abstract: Nowadays, discovering new skeleton antifungal drugs is the direct way to address clinical fungal infections. Pyrylium salt SM21 was screened from a library containing 50,240 small molecules. Several studies about the antifungal activity and mechanism of SM21 have been reported, but the structure–activity relationship of pyrylium salts was not clear. To explore the chemical space of antifungal pyrylium salt SM21, a series of pyrylium salt derivatives were designed and synthesized. Their antifungal activity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The synthesis of new structural antifungal compounds and elucidation of their antifungal mechanisms are urgently needed. In this study, through structural modification of SM21, we synthesized a compound, xy12, with stronger activity and lower toxicity ( 17 ). The skeleton structure of SM21 is pyrylium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of new structural antifungal compounds and elucidation of their antifungal mechanisms are urgently needed. In this study, through structural modification of SM21, we synthesized a compound, xy12, with stronger activity and lower toxicity ( 17 ). The skeleton structure of SM21 is pyrylium.…”
Section: Discussionmentioning
confidence: 99%
“…However, its specific mechanism of action is still unclear. In our study, based on the structure of SM21, we obtained a new lipophilic pyrylium salt, xy12, which showed improved antifungal activity and reduced cytotoxicity both in vitro and in vivo ( 17 ). In the present study, integrated analysis of the transcriptome and metabolome revealed that oxidative phosphorylation could be suppressed by treatment with xy12.…”
Section: Introductionmentioning
confidence: 99%
“…All solvents and reagents were obtained commercially and used without any further purification unless otherwise noted. 1 H and 13 C NMR spectra were collected at room temperature using a 400 MHz Bruker Avance III Spectrometer. Mass spectra were taken on 20 μg/mL methanol solutions using an Advion Expression Compact Mass Spectrometer.…”
Section: General Informationmentioning
confidence: 99%
“…3 Pyrylium salts (Figure 1) are used in a wide variety of applications, including organic synthesis, [4][5][6][7][8][9] photocatalysis, [10][11][12][13] and medicine. 14,15 In the field of photocatalysis, pyryliums have been used as effective replacements for precious metal catalysts in [2+2] and [4+2] cycloadditions as well as Diels-Alder reactions and ring-opening metathesis polymerization of norbornene. 16 Despite these promising applications, the current library of known pyrylium salts is largely limited to salts which absorb violet light and appear yellow 17 .…”
mentioning
confidence: 99%
“…Additionally, the local formulations may lead to itching, redness with low efficacy. Advanced agents improve tolerability and widen the toxic therapeutic ratio [10,11] .…”
Section: Introductionmentioning
confidence: 99%